2014
DOI: 10.3892/ijo.2014.2808
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IL-6/STAT3 axis and targeting Axl and Tyro3 receptor tyrosine kinases by apigenin circumvent taxol resistance in ovarian cancer cells

Abstract: Abstract.Ovarian cancer is the number one cause of death from gynaecological malignancy. Platinum-based and taxolbased chemotherapy has been used as a standard therapy, but intrinsic and acquired resistance to chemotherapy is a major obstacle to treat the disease. In the present study, we found that in the chemoresistant ovarian cancer SKOV3/TR cells, interleukin-6 (IL-6), IL-6 receptor and signal transducers and activators of transcription 3 (STAT3) expression as well as STAT3 phosphorylation were upregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 36 publications
1
60
0
Order By: Relevance
“…8,9 Constitutive STAT3 activation has been linked to resistance to standard-of-care chemotherapies, supporting that the development of paclitaxel resistance in ovarian cancers involves transcriptional control of drug resistance genes. 8 In keeping with this, inhibition of STAT3 using stattic, a small-molecule inhibitor, blocks STAT3 phosphorylation, decreases cell viability, and reduces clonogenicity of paclitaxel-resistant ovarian cancer SKOV3/TR cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Constitutive STAT3 activation has been linked to resistance to standard-of-care chemotherapies, supporting that the development of paclitaxel resistance in ovarian cancers involves transcriptional control of drug resistance genes. 8 In keeping with this, inhibition of STAT3 using stattic, a small-molecule inhibitor, blocks STAT3 phosphorylation, decreases cell viability, and reduces clonogenicity of paclitaxel-resistant ovarian cancer SKOV3/TR cells.…”
mentioning
confidence: 99%
“…8 In keeping with this, inhibition of STAT3 using stattic, a small-molecule inhibitor, blocks STAT3 phosphorylation, decreases cell viability, and reduces clonogenicity of paclitaxel-resistant ovarian cancer SKOV3/TR cells. 9 Recently, we found that Janusactivated kinase 2 (JAK2) gene was significantly upregulated in OC3/TAX300 cell line and in patient tissues. Because JAK2 can induce STAT3 activation, this suggests that the JAK2-STAT3 pathway might be related to paclitaxel resistance in ovarian cancers.…”
mentioning
confidence: 99%
“…Signal transducer and activator of transcription 3 (Stat3) proteins, a member of the Stat family, has been shown to mediate a wide spectrum of cellular responses, including apoptosis, proliferation, pluripotency, invasion and angiogenesis (VEGF) [6], and be closely linked with tumorigenesis www.impactjournals.com/oncotarget/ Oncotarget, Advance Publications 2018 [7]. In addition, Stat3 is activated by the upregulation of upstream signaling molecules such as IL-6 [8] which can also stimulate expression of the vascular endothelial growth factor (VEGF) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several drug-treated 'oncogeneaddicted' cancer cells induce a positive feedback loop leading to STAT3 activation, consequently promoting cell survival and limiting overall drug response. For example, overactivation of STAT3 is associated with resistance to chemotherapy (i.e., taxol [137]) and targeted agents used in a variety of tumors, including the anti-EGFR mAb cetuximab, the anti-HER2/neu receptor mAb trastuzumab and TKIs erlotinib, sunitinib, sorafenib, crizotinib and imatinib mesylate [138][139][140][141]. The combined use of these agents with STAT3 inhibitors should be investigated in clinical trials, even to understand if STAT3 inhibitors should be administered from the start of targeted therapy to reduce primary resistance or at time of acquired resistance.…”
Section: Expert Opinionmentioning
confidence: 99%